Entre ruas que subjetivam, registros do governo da vida e da morte na cidade - Silva, Wanderson Vilton Nunes da (2013)
From July 2010, the newspapers of Alagoas and the country begin to report murders of homeless people in the state. In that year, the national and local press took up the event, linking them to a massacre. From a non-individualistic perspective of Social Psychology, considering the contributions of Michel Foucault and of the philosopher and jurist Giorgio Agamben, we take these murders as an event. Taking as reference the readings of Foucault, who conceives the forms of subjectivity as associated with the modes of governing the subjects and with the production of subjectivities from power technologies, this dissertation is circumscribed in a genealogical perspective. It aims to produce a critique of the present and of the modes of life and death government from the problematization of the deaths of homeless people in Maceio, recorded by the media and other public documents. In order to accomplish this, from the perspective of Social Psychology and Foucault studies, we analyze this event from the concepts of modes of subjectivity, government and relations of power / knowledge. We are interested in constructing historical crossings, from the speeches in media texts and public documents published during the period between July 2010 and August 2012, when the murders of homeless people in Maceio started running in the media as true fact in life of the polis and the documents that attempt to systematize this event were developed. We start from the Foucaultian discourse analysis related to the relations of power / knowledge, considering three theoretical-conceptual analyzers related to public documents and media texts in this work: 1) the abandonment of life and the production of bare life, 2) drugs as a biopolitical apparatus of life regulation, and 3) the production of deaths and the government strategies for the street population. From the historical analysis of what we call event in this dissertation, we intend to contribute critically with public policies that aim the various modes of existing in the city, focusing on the contributions that the production of knowledge in Social Psychology can make in thinking urban spaces, modes of government and the processes of subjectivity.